Moodle in German Language Learning: Advantages and Disadvantages - Nara Faiz Saskara Saskara; Pepen Permana; Irma Permatawati (Didaktika: Jurnal Kependidikan, 2025)
This study investigates the use of VKZ (Virtuelles Klassenzimmer), a Moodle based online learning platform, in the German language Education Study Program at Universitas Pendidikan Indonesia. As digital learning tools become increasingly vital in education—especially post-pandemic—understanding their efficacy and student perceptions is critical for optimizing blended and remote learning environments. The study aimed to explore students’ perceptions of VKZ, identifying its advantages and disadvantages to inform future improvements. Conducted as a qualitative case study, the research purposively sampled 240 students enrolled in German language courses. Data were collected through structured surveys and analyzed using thematic analysis to identify recurring patterns in student feedback. Findings revealed that students generally perceived VKZ positively, citing benefits such as accessibility, flexibility, and engaging features like repeatable exercises, multimedia integration, and immediate feedback. However, challenges included technical issues (e.g., server instability, poor mobile compatibility, and quiz errors), which disrupted learning, as well as limited direct interaction with lecturers and insufficient feedback for open-ended tasks. The study underscores the need for enhanced technical support, system reliability, and interactive features to maximize VKZ’s effectiveness. The findings highlight the need for continuous improvement of e-learning platforms to meet learners' dynamic needs in the digital age.